A questionnaire on pelvic floor dysfunction postpartum - Luthander, Charlotte (Springer-Verlag, 2010)
INTRODUCTION AND HYPOTHESIS: The incidence of obstetric anal sphincter injuries is used in Sweden as a measurement of quality of care and this might influence the reporting. However, the correlation between reported diagnosis of pelvic floor injury at delivery and pelvic floor symptoms a year later is unknown. A questionnaire could identify such symptoms and provide beneficial feedback to obstetrical practices. METHODS: We made a cross-sectional study by sending out a questionnaire about pelvic floor dysfunction to 599 women depending on reported injury at delivery. The answers provided by the groups were then compared. RESULTS: The questionnaire identified women with pelvic floor dysfunction. Anal incontinence was most common among women with obstetric anal sphincter injuries but also occurred among women delivered vaginally without known tears. CONCLUSION: We suggest that a questionnaire is used 12–18 months after delivery to establish the short-time outcome in terms of pelvic floor dysfunction.